Molecular Communication Between Neuronal Networks and Intestinal Epithelial Cells in Gut Inflammation and Parkinson's Disease - Drobny, Alice; Ngo, Phuong A.; Neurath, Markus F.; Zunke, Friederike; López-Posadas, Rocío (Frontiers in Medicine, 2021)
Intestinal symptoms, such as nausea, vomiting and constipation, are common in Parkinson’s disease patients. These clinical signs normally appear years before the diagnosis of the neurodegenerative disease, preceding the occurrence of motor manifestations. Moreover, it is postulated that Parkinson’s disease might originate in the gut, due to a response against the intestinal microbiota leading to alterations in alpha-synuclein in the intestinal autonomic nervous system. Transmission of this protein to the central nervous system is mediated potentially via the vagus nerve. Thus, deposition of aggregated alpha-synuclein in the gastrointestinal tract has been suggested as a potential prodromal diagnostic marker for Parkinson’s disease. Interestingly, hallmarks of chronic intestinal inflammation in inflammatory bowel disease, such as dysbiosis and increased intestinal permeability, are also observed in Parkinson’s disease patients. Additionally, alpha-synuclein accumulations were detected in the gut of Crohn´s disease patients. Despite a solid association between neurodegenerative diseases and gut inflammation, it is not clear whether intestinal alterations represent cause or consequence of neuroinflammation in the central nervous system. In this review, we summarize the bidirectional communication between the brain and the gut in the context of Parkinson’s disease and intestinal dysfunction/inflammation as present in inflammatory bowel disease. Further, we focus on the contribution of intestinal epithelium, the communication between intestinal epithelial cells, microbiota, immune and neuronal cells, as well as mechanisms causing alterations of epithelial integrity.